2003
DOI: 10.1093/brain/awg231
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament inclusion body disease: a new proteinopathy?

Abstract: We describe four cases of a new clinicopathological entity presenting with either a frontotemporal dementia or corticobasal degeneration syndrome with a mean age of onset of 45 years (range 41-50) characterized pathologically by deposition of neurofilament proteins. All four patients had a rapidly progressive course and have become mute and non-ambulatory, and three have died after mean illness duration of only 3 years (range 2 1/2 -4). Both structural (MRI) and functional (PET and SPECT) imaging demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
3
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(149 citation statements)
references
References 47 publications
6
137
3
3
Order By: Relevance
“…α-Internexin has recently been identified as a major component of the pathological inclusions of the frontotemporal dementia, neuronal intermediate filament inclusion disease (NIFID) (Figure 2). The signature lesion of this disease is the neuronal cytoplasmic inclusion, which is tau-and α-synuclein negative, variably ubiquitinated, and contains epitopes of all type IV IF proteins [59][60][61]. In addition to NFs in swollen axons and spheroids in ALS, peripherin has also been demonstrated by immunohistochemistry (IHC) in the ubiquitinated inclusions of ALS [62].…”
Section: Neuronal Ifs and Diseasementioning
confidence: 99%
“…α-Internexin has recently been identified as a major component of the pathological inclusions of the frontotemporal dementia, neuronal intermediate filament inclusion disease (NIFID) (Figure 2). The signature lesion of this disease is the neuronal cytoplasmic inclusion, which is tau-and α-synuclein negative, variably ubiquitinated, and contains epitopes of all type IV IF proteins [59][60][61]. In addition to NFs in swollen axons and spheroids in ALS, peripherin has also been demonstrated by immunohistochemistry (IHC) in the ubiquitinated inclusions of ALS [62].…”
Section: Neuronal Ifs and Diseasementioning
confidence: 99%
“…Neuronal intermediate filament (IF) inclusion disease (NIFID) is a novel neurological disease with a clinically heterogeneous phenotype including progressive early-onset dementia, pyramidal and extrapyramidal signs. Grossly, there is focal atrophy of the frontal lobes, and to a lesser degree the temporal and parietal lobes, and, microscopically, there are intraneuronal, cytoplasmic, neuronal IF inclusions which contain neither tau nor α-synuclein [2,4,12,15,21,38]. The inclusions are present in neocortex, where clusters of inclusions have been reported [3], subcortical nuclei and spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous reports failed to detect abnormal protein deposits in brains of patients with FTD-3, a recent study demonstrated the presence of granular NCIs that were immunoreactive for ubiquitin and p62, but negative for TDP-43 and tau, predominantly in the dentate granule cells of the hippocampus (Fig. 4e) The neuropathological findings in NIFID are heterogeneous, but have a number of consistent features (Refs 148,150,151,152,153,154,155,156,157). Chronic degenerative changes may affect a variety of cortical and subcortical regions, with the frontal and temporal lobes and caudate nucleus most consistently and severely involved.…”
Section: Ftld-upsmentioning
confidence: 83%